THE IMPACT OF USER EXPERIENCE AND CUSTOMER SATISFACTION ON CUSTOMER LOYALTY IN BCA MOBILE BANKING - Velika, Yoshi; Adnas, Diny Anggriani (ZONAsi: Jurnal Sistem Informasi, 2025)
This research examines the relationship between user experience and its effect on customer satisfaction and loyalty in the context of BCA Mobile. The examination outlines the direct and indirect impacts of user experience on customer loyalty, with customer satisfaction serving as a crucial mediating factor. A quantitative research approach was utilized, collecting data from 161 qualified participants through a standardized questionnaire that used a 4-point Likert scale. The results demonstrate that user experience had a considerable impact on customer satisfaction and customer loyalty. Additionally, it was determined that customer satisfaction has a direct positive effect on loyalty and also plays a crucial mediating role between user experience and loyalty. These results emphasize the essential importance of improving customer satisfaction to boost customer loyalty. The findings indicate that enhancing user experience is a strategic method to boost customer engagement and retention amid the competitive environment of mobile banking services.